Gambang Semarang and Chinese-Indonesian Identity: Implications for Multicultural Education - Eko Raharjo; Fathur Rochman; Raqib Chowdhury; Hafid Zuhdan Bahtiar; Antonius Edi Nugroho (Harmonia: Journal of Arts Research and Education, 2026)
This study examines how the Gambang Semarang group, a mix of Chinese and Javanese performing arts from Semarang, Indonesia, helps Chinese-Indonesians find their identity and teaches about cultures. The research took six months. Used many methods, such as watching the group perform, talking to people, reviewing papers, and discussing with groups. These activities took place in a school, two community places, and 18 shows, with 42 people taking part. The study draws on Bhabha’s ideas on space and Banks’s five parts of multicultural education. It finds three ways people deal with their identity. First, mixing music styles. This is not equal because some groups have more power. Second, using language to help deal with memories. Third, showing who they are in temples, government places, and festivals. The study shows that the mix of cultures in Gambang Semarang is not equal but is a negotiated deal due to differences between Javanese and Chinese people. The group can help teach about cultures in many ways, but this is not always done well because schools do not adequately support it, and teachers are not prepared. The study contributes to the study of space by explaining how cultural mixing operates across domains such as history, rules, symbols, and personal relationships. It also introduces the idea of “hybridity,” which connects cultural mixing with teaching. It offers ideas for incorporating mixed arts into teaching in Southeast Asia. It argues that teachers need training and guidelines that recognize mixed arts as important for learning and identity formation.